Ukama Ustawi Community of Spirit Design - Reos Partners (2022)
This document outlines the design of the Ukama Ustawi Community of Spirit (UU CoS). The design was developed following a participatory process that included a survey distributed to the entire UU community, a Mentimeter poll conducted at the Core Partners meeting held on the 9 September 2022 and a series of short dialogue interviews. This process helped to surface how this Community can best serve the UU initiative partners as well as how the UU team (staff and partners) want to work together (both the agreements around the quality and principles for engagement, as well as the practical aspects such as cadence and types of meetings (e.g., in-person, virtual, etc.). These insights were synthesized into a report and served as inputs and departure points during a two session COS co-design workshop that was held on the 8 and 9 December 2022. The design elements that were clarified during this workshop series and are reflected in this document are: 1. the purpose of the COS (why does the COS exist?) 2. its operating principles (how the UU COS team wants to be with each other) and, 3. a work plan for 2023 (what the UU COS will be doing in 2023).